Sarcopenia, frailty, and elective surgery outcomes in the elderly: an observational study with 125 patients (the SAFESOE study) - de Salles, Isabel Chateaubriand Diniz; Sernik, Renato; da Silva, José Luiz Padilha; Taconeli, Cesar; Amaral, Ana Alice; de Brito, Christina May Moran; Bierrenbach, Ana Luiza (Frontiers in Medicine, 2023)
Abstract Background Sarcopenia is a syndrome characterized by loss of muscle mass, strength and function. Frailty, a state of vulnerability with diminished reserves. The measurement of perioperative risk does not include the assessment of these variables, as little is known about how these conditions impact each other. Methods Observational study with a cross-sectional and a prospective cohort component. Elderly people over 60 years of age, able to walk and to independently perform activities of daily living were consecutively recruited in the preoperative period of non-emergency surgical procedures. Frailty was measured by the modified frailty index (mFI-11). Sarcopenia was measured by: (1) thickness and echogenicity on ultrasound; (2) handgrip strength on dynamometry and (3) gait speed. Data obtained from eight muscle groups were submitted to Principal Component Analysis. Postoperative complications were measured using the Clavien-Dindo scale. Follow-up was performed for one year to record readmissions and deaths. Results Between February and May 2019, 125 elderly people were recruited, median age of 71 years (IQR 65-77), 12% of whom were frail. Frailty was associated with older age, use of multiple medicines, presence of multimorbidity and greater surgical risk according to the American Society of Anesthesiologists (ASA) scale, in addition to lower gait speeds and lower handgrip strength. Frailty was also independently associated with smaller measurements of muscle thickness but not with echogenicity, and with longer hospital and Intensive care unit (ICU) stays. Prevalence of sarcopenia was 14% when considering at least two criteria: low walking speed and low handgrip strength. For muscle thickness, lower values were associated with female gender, older age, frailty, lower gait speeds and lower muscle strength, higher proportion of postoperative complications and higher occurrence of death. For echogenicity, higher values were related to the same factors as those of lower muscle thickness, except for postoperative complications. Lower gait speeds and lower handgrip strength were both associated with higher proportions of postoperative complications, and longer hospital stays. A higher mortality rate was observed in those with lower gait speeds. Conclusions Sarcopenia was associated with frailty in all its domains. Unfavorable surgical outcomes were also associated with these two conditions.